Analisis Implementasi Prosedur Akuntansi Kas Kecil dalam Operasional Harian PT XYZ - Nanda Kannisa Fatimah Azzahrah; Erna Sulistyowati (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Asset management, especially cash, is important for the development of the company, one way that companies control cash out, especially for those with relatively small amounts to be paid regularly, can be done by forming petty cash. The purpose of this study is to analysis the petty cash procedure at PT XYZ to find out how the petty cash recording system at PT XYZ and what supporting documents are used to recognize petty cash expenditures. The research was conducted using a Qualitative Case Study approach. The results of the analysis show that the petty cash procedure at PT XYZ has been running quite well in controlling the company's operational expenses, especially for expenses with a relatively small nominal, Petty cash expenditures at PT XYZ use the fluctuation method in recording petty cash.